1995
DOI: 10.1093/hmg/4.2.189
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic mosaicism in sperm is associated with intergenerational (CAG)n changes in Huntington disease

Abstract: We have analysed the CAG repeat in the Huntington disease (HD) gene in sperm and blood from 20 unrelated HD patients. Although the CAG repeat displayed significant mosaicism in sperm from all individuals, there were marked differences in the degree of repeat instability. Individuals who had either inherited or transmitted an expanded CAG repeat displayed the highest levels of repeat mosaicism, whereas individuals who had inherited or transmitted a contracted repeat had very limited CAG mosaicism in sperm. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 17 publications
(20 reference statements)
2
42
0
2
Order By: Relevance
“…We observed a variation of 13 to 17 CAGs for gene 14, and 10 or 11 CAGs for gene 25. This could reflect allelic mosaisism expression observed previously for this kind of gene in human testis (Zühlke et al 1993;Telenius et al 1995;Zhang et al 1995), which may occur in meiosis during spermatogenesis.…”
Section: Discussionsupporting
confidence: 63%
“…We observed a variation of 13 to 17 CAGs for gene 14, and 10 or 11 CAGs for gene 25. This could reflect allelic mosaisism expression observed previously for this kind of gene in human testis (Zühlke et al 1993;Telenius et al 1995;Zhang et al 1995), which may occur in meiosis during spermatogenesis.…”
Section: Discussionsupporting
confidence: 63%
“…1A). The ability to correlate the length of the CAG expansion to clinical phenotype uncovered the molecular basis for genetic anticipation (Telenius et al 1993;Telenius et al 1995). Anticipation in HD referred to the puzzling phenomenon whereby inheritance of the mutant HTT allele through the male germ line often led to a more severe clinical course than inheritance through the female germ line.…”
Section: Huntington's Disease: a Clinical Overview Of Genotype -Phenomentioning
confidence: 99%
“…A high level of mosaicism was commonly observed in sperm, with this mosaicism overlapping the sizes inherited by the offspring, suggesting that intergenerational instability results mainly from germinal instability in the father (8,12,25,34,38,52,53). However, several studies, including one on fragile X fetuses and one on transmission in Friedreich ataxia families, suggested that intergenerational length changes could also involve a postzygotic instability event (13,14,37).…”
mentioning
confidence: 99%